Expression and Function of Ephrin-B1 and Its Cognate Receptor EphB2 in Human Abdominal Aortic Aneurysm - Aiji Sakamoto; Masaaki Kawashiri; Hatsue Ishibashi-Ueda; Yuka Sugamoto; Tsuyoshi Yoshimuta; Takeo Higashikata; Hitoshi Ogino; Hayato Tada; Tetsuo Konno; Kenshi Hayashi; Masakazu Yamagishi (International Journal of Vascular Medicine)
We examined the expression of ephrin-B1 and its cognate receptor EphB2, key regulators of angiogenesis and embryogenesis, in human abdominal aortic aneurysm (AAA) and analyzed their functional roles in cell migration. From 10 patients (9 males and 1 female; age, 68.5±2.4) who underwent vascular surgery for AAA, we obtained AAA and adjacent control tissues. Using real-time RT-PCR, we analyzed expression of ephrin-B1 and EphB2. We also histologically localized these molecules in AAA tissues. Finally, effects of ephrin-B1 and EphB2 on inflammatory cell chemotaxis were examined by cell migration assay. Expression levels of ephrin-B1 (0.410±0.046 versus 1.198±0.252, 𝑃=0.027) and EphB2 (0.764±0.212 versus 1.272±0.137, 𝑃=0.594) were higher in AAA than normal control. Both ephrin-B1 and EphB2 were expressed in macrophages, T lymphocytes, and endothelial cells within AAA. In chemotaxis assay, ephrin-B1 and EphB2 inhibited mononuclear-cell chemotaxis induced by stromal derived factor-1 down to 54.7±12.7% (𝑃=0.01) and 50.7±13.1% (𝑃=0.01), respectively. These data suggest that ephrin-B1 and EphB2 might be functional in human adult inflammatory cells and involved in the pathogenesis of AAA, although specific roles of these molecules should further be sought.